Emmanuel Levinas and the politics of non-violence - Tahmasebi-Birgani, Victoria (University of Toronto Press, 2014)
In this book, Victoria Tahmasebi-Birgani provides the first examination of the applicability of Emmanuel Levinas' work to social and political movements